Subcapsular Nephrectomy, Ureterectomy, Partial Cystectomy Due to Forgotten Ureteral Stent: Case Report (Annals of Medical Research, 2021)
None
Keywords: Forgotten Ureteral Stent; Stone Formation; Management.